Drought-responsive WRKY transcription factor genes IgWRKY50 and IgWRKY32 from Iris germanica enhance drought resistance in transgenic Arabidopsis - Zhang, Jingwei; Huang, Dazhuang; Zhao, Xiaojie; Zhang, Man; Wang, Qian; Hou, Xueyan; Di, Dongliu; Su, Beibei; Wang, Shaokun; Sun, Pai (Frontiers in Plant Science, 2022)
Drought greatly affects the growth and development of garden plants and affects their ornamental value. WRKY transcription factors make up one of the largest transcription factor families in plants and they play an important role in the plant response to drought stress. However, the function of the WRKY gene in response to drought stress in Iris germanica, which is commonly used in landscaping, has not been studied. In this study, we isolated two WRKY transcription factor genes from Iris germanica, IgWRKY50 and IgWRKY32, which belong to Group II and Group III of the WRKY family, respectively. IgWRKY50 and IgWRKY32 could be induced by PEG-6000, high temperature and ABA in Iris germanica. IgWRKY50 and IgWRKY32 could quickly respond to drought and they peaked at 3 h after PEG-6000 treatment (19.93- and 23.32-fold). The fusion proteins IgWRKY50-GFP and IgWRKY32-GFP were located in the nucleus of mesophyll protoplasts of Arabidopsis. The overexpression of the IgWRKY50 and IgWRKY32 genes improved the osmotic tolerance of transgenic Arabidopsis, mainly exhibited by the transgenic plants having a higher germination rate and a longer total root length on 1/2 MS medium containing mannitol. Under PEG-6000 stress, the transgenic plants had higher stomatal closure than the wild type (WT). Under natural drought stress, the water loss rate of the isolated leaves of transgenic Arabidopsis was lower than that of WT, the contents of proline (Pro) and soluble protein (SP) and the activities of superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) in the transgenic plants were higher, but the content of malondialdehyde (MDA) was lower. Furthermore, the expression of several stress-related genes (RD29A, DREB2A, PP2CA and ABA2) was significantly increased in IgWRKY50- and IgWRKY32- overexpressing transgenic Arabidposis plants after drought treatment. These results suggest that IgWRKY50 and IgWRKY32, as two positive regulators, enhance the drought resistance of transgenic Arabidopsis by mediating the ABA signal transduction pathway. IgWRKY50 and IgWRKY32 can be used as candidate genes for molecular breeding of drought resistance in Iris.